SPIRITUAL AND EDUCATIONAL ASPECTS OF THE CONSTRUCTION OF THE THIRD REVIVAL IN OUR COUNTRY (E Global Congress, 2023)
This article reveals the spiritual and educational aspects of the construction of the Third Renaissance in our country on the basis of historical foundations and existing opportunities.